Pengaruh Electronic Word of Mouth terhadap Sikap Merek dan Niat Beli Merek pada Produk Uniqlo di Surakarta - Putra Nurmahendra; Anton Agus Setyawan (Jurnal Informatika Ekonomi Bisnis, 2023)
The aim of this research is to expand the eWOM literature that still exists on various social networks. This research takes TikTok as an online networking tool which aims to test the influence of social eWOM on brand attitudes and purchase intentions. Positive social electronic word of mouth (eWOM) on brand attitudes and brand purchase intentions, the type of research used is quantitative research. The cross-sectional method was used to test the research model involving consumers of Uniqlo products in urban areas. The results of this research are that Social E-WOM has a significant positive influence on Brand Attitude so that the first hypothesis is accepted. This is because the t-statistic value is 5.669>1.96 and the p-value is 0.000<0.05. Social E-WOM is word of mouth marketing between consumers via social media. Social E-WOM has a positive and significant influence on Purchase Intention so that the second hypothesis is accepted. This is because the t-statistic value is 3.464>1.96 and the p-value is 0.001<0.05. This is because the t-statistic value is 7.003>1.96 and the p-value is 0.000<0.05. Purchase intention is a consumer's desire to buy a product or service. Meanwhile, consumer attitudes towards brands are how consumers view the product. If consumers view the brand as good, then consumers will have the intention to buy the product. So consumers' purchasing intentions will also arise from responding to the product.